On the multiplicative order of elements in Wiedemann's towers of finite fields - Popovych, R. (Carpathian Mathematical Publications, 2015)
We consider recursive binary finite field extensions $E_{i+1} =E_{i} (x_{i+1} )$, $i\ge -1$, defined by D. Wiedemann. The main object of the paper is to give some proper divisors of the Fermat numbers $N_{i} $ that are not equal to the multiplicative order $O(x_{i} )$.